307 Awareness and Reporting of Needle Stick Injury Amongst Junior Doctors in a General Surgery Department. (12th October 2021) - Mistry, R; Mahamud, I
Abstract: Introduction: This audit was performed to see if a new cohort of junior doctors in a general surgery department had received legally required sharps injury training, assess knowledge on what to do if a needle stick/splash injury were to occur; and to provide necessary training. Method: Questionnaires about trust needle stick policy training including current job grade, awareness of general principles, reporting of previous needle stick injuries and barriers to reporting of needle stick injuries were filled in. Training was provided on needle free devices and trust needle stick/splash injury protocol. After training, a second questionnaire was filled in to see if there was better understanding of the trust protocol and the necessary steps after injury. The same group of junior doctors were re-audited at a later date to see if the knowledge gained from training had been retained. Results: All junior doctors (total of 11) in general surgery reported receiving no formal needle stick/splash training since starting at the trust on the trust policy and no formal induction on needle-free devices and what to do in the event of a needle stick injury since starting at the trust. All doctors felt aware of what to do after training provided with time pressures being identified as a barrier for not reporting all needle stick injuries. Re-audit one month later demonstrated all doctors had awareness of the trusts needle stick/splash injury protocol. Conclusions: The training provided was effective in providing legally required training and improving staff and patient safety.